Inflammatory and Hemolytic Responses of Microaxial Flow Pump Temporary Ventricular Assist Devices via Axillary Access in Cardiogenic Shock - Leonie Schmack; Sadeq Ali-Hasan-Al-Saegh; Alexander Weymann; Nikolaus Pizanis; Payam Akhyari; Alina Zubarevich; Jasmin Sarah Hanke; Aron-Frederik Popov; Arjang Ruhparwar; Tienush Rassaf; Markus Kamler; Peter Luedike; et al. (Medicina)
Background and Objectives: The use of temporary left ventricular assist devices (tLVADs) for patients suffering from cardiogenic shock (CS) is becoming more common. This study examines the indications and outcomes of microaxial flow pumps (Impella®, Abiomed Inc., Danvers, MA, USA) when cannulated through the axillary artery in patients with severe CS, with a particular focus on acute phase reactions and hemolytic responses. Materials and Methods: This single-center, retrospective cohort involved patients who received microaxial Impella implantation via the axillary artery from 2020 to 2022 (n = 47). Results: Among the patients, 66% (N = 31 cases) were treated with the Impella 5.5, 25.5% (N = 12 cases) with the Impella 5.0, and 8.5% (N = 4 cases) with the Impella CP. Additionally, 28% were managed using the ECMELLA concept. The mean length of time for Impella support was 8 days. The overall 30-day survival rate was 78%, with no significant differences observed between the ECMELLA group and the various Impella types. At 30 days post-therapy, 47% of survivors no longer required mechanical support, while 26% were upgraded to a durable LVAD. Interleukin-6 (IL-6) levels were significantly lower in patients receiving Impella 5.5 (n = 17 vs. 12) immediately following implantation (p = 0.03) compared with those with smaller devices. Haptoglobin levels were significantly higher in the Impella 5.5 group (n = 17 vs. 11, p = 0.02), with overall lower rates of hemolysis (45.1%, p < 0.01). Conclusions: The mortality rate in critical CS appears reduced with axillary artery implantation of Impella devices relative to existing literature. A full-flow microaxial pump (Impella 5.5) seems advantageous regarding systemic inflammatory response syndrome (SIRS) and acute hemolysis, indicated by lower IL-6 and higher haptoglobin levels, compared with smaller Impella devices. A tailored escalation/de-escalation concept using axillary access for different mAFP types appears feasible and safe.